The Greek urban block since the establishment of the Greek State in 19th century. A chronicle about morphology and urban form. - Oikonomou, Maria (International Planning History Society Proceedings, 2016)
Based on literature and archival research along with specific plans, the study considers the different transformations of the Greek urban block in relation to street network, built and open space. Case studies such as Thessaloniki, Athens, Patra, Serres, offer the opportunity to highlight the evolution of the Greek urban block through representative examples of urban development in specific periods of Greek history; in the neoclassic city of the 19th century, during the beginning of 20th century, during the interwar period (1923 - 1940) and in the post-war city during 1950s and 1970s. The investigation focuses on the general historical framework connected to urban development, whereas specific masteplans showcase the practice of each period respectively. Moreover, the study highlights parameters, which form, reform or transform the urban blocks, such as planning principles and design tools. The objective of this research is to analyze characteristics and qualities of the morphology of urban blocks in order to understand its importance in the organization of the city.